Resolving XUV induced femtosecond and attosecond dynamics in polyatomic molecules with a compact attosecond beamline. (November 2015) - Loriot, V; Marciniak, A; Quintard, L; Despré, V; Schindler, B; Compagnon, I; Concina, B; Celep, G; Bordas, C; Catoire, F; Constant, E; Lépine, F
Abstract: XUV induced dynamics in molecules is still largely unexplored while experimental and theoretical tools are becoming available in several labs. In this work, we present a compact XUV beamline designed to induce and probe femtosecond and attosecond dynamics in gas samples (from atoms to complex molecular species). The induced processes are studied with time-resolved photoelectron or/and photoion imaging. The characterization of the performances of the experimental setup is presented. We show experimental results obtained in naphthalene molecule showing femtosecond and attosecond time-resolved photoelectron imaging experiments allowing electron wavepacket phase measurements.